2023
DOI: 10.1101/2023.07.05.547765
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sparse spatial scaffolding for visual working memory

Abstract: Selective attention enables the prioritisation of task-relevant visual information, including among internal contents in working memory. Studies targeting the foundational mechanisms of covert selective attention often consider situations where to-be-attended and to-be-ignored visual contents are presented or memorised in distinct directions from fixation — rendering direction sufficient for covert selection. Yet, in everyday life, direction alone is typically insufficient for selection because multiple potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…Interestingly, in a recent study on gaze shifts during memory retrieval under maintained fixation, Liu et al, (2023) showed that when the direction is a unique feature of each item (one item per direction) then the distance to the fixation cross is not reflected in the amplitude of gaze shifts. However, when the direction is not unique (two items per direction) then gaze shifts also reflect the distance (longer amplitudes for the far item compared to the near item).…”
Section: Characteristics Of Internally Coupled Eye Movementsmentioning
confidence: 99%
“…Interestingly, in a recent study on gaze shifts during memory retrieval under maintained fixation, Liu et al, (2023) showed that when the direction is a unique feature of each item (one item per direction) then the distance to the fixation cross is not reflected in the amplitude of gaze shifts. However, when the direction is not unique (two items per direction) then gaze shifts also reflect the distance (longer amplitudes for the far item compared to the near item).…”
Section: Characteristics Of Internally Coupled Eye Movementsmentioning
confidence: 99%